Inherent Irreversibility of Mixed Convection within Concentric Pipes in a Porous Medium with Thermal Radiation - Oluwole Daniel Makinde; Adetayo Samuel Eegunjobi (Journal of Mathematical and Fundamental Sciences, 2021)
This work investigated the thermal putrefaction and inherent irreversibility in a steady flow of an incompressible inconstant viscosity radiating fluid within two concentric pipes filled with a porous medium. Following the Brinkmann-Darcy-Forchheimer approach, the nonlinear differential equations governing the model were obtained. The model boundary value problem was addressed numerically via a shooting quadrature with the Runge-Kutta-Fehlberg integration scheme. The effects of diverse emerging parameters on the fluid velocity, temperature, skin friction, Nusselt number, entropy generation rate and the Bejan number are provided in graphs and discussed in this paper.